2011
DOI: 10.1111/j.1445-5994.2011.02426.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological complications following initiation of lenalidomide in a patient with chronic lymphocytic leukaemia

Abstract: Off-label use of lenalidomide (Len) in chronic lymphocytic leukemia (CLL) is becoming increasingly frequent. When compared with thalidomide, Len has been reported to have more potent anti-tumour activity and a better safety profile. However, dermatological side-effects are known to occur with both drugs. Clinical trial design often precludes precise quantification of infrequent toxicities and studies frequently report only grade 3-4 toxicities without a detailed description of rashes, leading to under-recognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…Sweet's syndrome is usually accompanied with evidence suggesting the onset, relapse or recurrence of the underlying malignancy in similar reports (3,5,(10)(11)(12). However, in our patient, the leukemia was in remission.…”
Section: Discussionsupporting
confidence: 71%
“…Sweet's syndrome is usually accompanied with evidence suggesting the onset, relapse or recurrence of the underlying malignancy in similar reports (3,5,(10)(11)(12). However, in our patient, the leukemia was in remission.…”
Section: Discussionsupporting
confidence: 71%
“…Another patient is reported with Sweet's syndrome in chronic lymphocytic leukemia who was treated with lenalidomide. The patient responded successfully to prednisone therapy (43). In a recently published study, the severity of lenalidomide-associated tumor flare reactions in CLL patients correlated directly with in vitro lenalidmide-induced upregulation of CD80 on CLL cells and CD69 expression on T cells (T-cell activation) and inversely with treatment-induced changes in T-cell numbers.…”
Section: Diagnositc Criteria For Medications-inducedmentioning
confidence: 81%
“…In a recently published study, the severity of lenalidomide-associated tumor flare reactions in CLL patients correlated directly with in vitro lenalidmide-induced upregulation of CD80 on CLL cells and CD69 expression on T cells (T-cell activation) and inversely with treatment-induced changes in T-cell numbers. A striking increase in the levels of IL-6 and TNF-α was seen in the patient with the most severe reaction, suggesting 'immune-activation' as the most likely culprit (43,44).…”
Section: Diagnositc Criteria For Medications-inducedmentioning
confidence: 90%
See 1 more Smart Citation
“…[7] N. Nateja et al reported dermatological complications in patients underwent lenalidomide treatment. [8] Imbruvica is another anticancer targeted therapy drug leading in the market, which works by the mechanism of irreversible binding to Bruton Tyrosine Kinase (BTK) molecule at BTK cysteine-481 ATP binding site, thereby inhibiting the phosphorylation of down-stream PLC-c2, and B-cell receptor signaling. However, a long period of administration of imbruvica can lead to chronic lymphocytic leukaemia, atrial fibrillation, bleeding risk, and side drug interactions.…”
Section: Introductionmentioning
confidence: 99%